30 HAEMOPHILUS INFLUENZAE FROM CHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS WITH EXACERBATION INDUCES MORE INFLAMMATION THAN COLONIZERS. (1st March 2005) - Look, D. C.; Chin, C. L.; Manzel, L. J.; Lehman, E. E.; Humlicek, A. L.; Shi, L.; Starner, T. D.; Denning, G. M.; Murphy, T. F.; Sethi, S.
Abstract : Infection by nontypable Haemophilus influenzae in the airway causes inflammation, and newly isolated strains of these bacteria are associated with an increased risk of disease exacerbation in patients with chronic obstructive pulmonary disease (COPD). In this study we questioned whether strains of H. influenzae associated with exacerbations cause greater inflammation than strains colonizing airways of COPD patients. Bacterial strains were obtained from COPD patients that underwent serial assessment of clinical status, sputum microbiology, and serum antibacterial antibody production. Exacerbation strains were defined as new isolates cultured during exacerbation of clinical symptoms with subsequent development of a homologous bactericidal antibody response. These strains were compared to colonization strains that were not associated with an increase in symptoms or new antibody production. We found that strains of H. influenzae associated with exacerbations caused more airway neutrophil recruitment than colonizer strains in an in vivo mouse model of airway infection. Experiments using an in vitro model of human primary airway epithelial cells revealed that exacerbation strains adhered significantly more to epithelial cells than colonizing strains. Exacerbating strains also induced greater release of interleukin-8 after interaction with airway epithelial cells, a response likely mediated by increased activation of both the nuclear factor-kappaB and p38 mitogen-activated protein kinase signaling pathways. The results indicate that H. influenzae isolated from patients with exacerbations of COPD induce more airway inflammation and likely have differences in virulence compared to colonizing strains. These findings support the concept that H. influenzae infecting the airway during COPD exacerbations mediate increased airway inflammation and contribute to decreased airway function.